2004
DOI: 10.1242/dev.01214
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac outflow tract defects in mice lacking ALK2 in neural crest cells

Abstract: Cardiac neural crest cells are multipotent migratory cells that contribute to the formation of the cardiac outflow tract and pharyngeal arch arteries. Neural crest-related developmental defects account for a large proportion of congenital heart disorders. Recently, the genetic bases for some of these disorders have been elucidated, and signaling pathways required for induction,migration and differentiation of cardiac neural crest have emerged. Bone morphogenetic proteins comprise a family of secreted ligands i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
162
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(170 citation statements)
references
References 80 publications
5
162
2
1
Order By: Relevance
“…Similar to Notch1, deletion of Gata5 or Alk2 in the OFT endothelial (endocardial) and endothelial‐derived mesenchymal cells is sufficient to cause BAV 27, 28, 29. In addition, the cardiac neural crest is critical for the development of the cardiac OFT because loss of BMP signaling via the receptor ALK2 has been shown to cause persistent truncus arteriosus, improper cardiac neural crest migration causes OFT defects, and the loss of Rho kinase signaling within neural crest cells gives rise to BAV 30, 31, 32. We did not observe any cardiac malformations using a neural crest–specific Cre driver to delete Notch1; however, this does not exclude the possibility that Notch1 in endothelial‐derived cells may be signaling to neural crest cells in the cardiac OFT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to Notch1, deletion of Gata5 or Alk2 in the OFT endothelial (endocardial) and endothelial‐derived mesenchymal cells is sufficient to cause BAV 27, 28, 29. In addition, the cardiac neural crest is critical for the development of the cardiac OFT because loss of BMP signaling via the receptor ALK2 has been shown to cause persistent truncus arteriosus, improper cardiac neural crest migration causes OFT defects, and the loss of Rho kinase signaling within neural crest cells gives rise to BAV 30, 31, 32. We did not observe any cardiac malformations using a neural crest–specific Cre driver to delete Notch1; however, this does not exclude the possibility that Notch1 in endothelial‐derived cells may be signaling to neural crest cells in the cardiac OFT.…”
Section: Discussionmentioning
confidence: 99%
“…The process of leaflet fusion is currently not well understood because leaflet fusion may occur early in cushion development or later during valve remodeling. Gata5 knockout mice display BAV, which is caused by an early fusion without leaflet thickening, unlike that of ALK2 mutant mice, which demonstrate thickened valve leaflets at early stages 27, 30. Some studies have concluded that BAV subtypes are a result of specific genetic etiologies because Gata5 −/− mice and Nos3 −/− mice display BAVs with right–noncoronary fusion 27, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Neural crest-specific inactivation of the type 1 bone morphogenetic protein receptor Alk2 causes a failure of outflow tract septation with deficient differentiation of neural crestderived SMCs (21). Inactivation of Semaphorin 3C, a secreted class 3 semaphorin, results in interruption of the aortic arch and persistent truncus arteriosus (25).…”
Section: Discussionmentioning
confidence: 99%
“…India ink was injected intracardially or into the descending aorta of mouse embryos by using a pulled glass pipette and immediately photographed as described (21).…”
Section: Methodsmentioning
confidence: 99%
“…Exogenous addition of recombinant BMP2 to cultured chicken neural crest cells highlights such effects as BMP2 appears to elicit the differentiation of several cell types, including smooth muscle cells (Abzhanov et al, 2003). Gene ablation studies in the mouse have identified BMP signals as regulator of the SMC differentiation from neural crest cells (Kaartinen et al, 2004). When embryonic stem (ES) cells are aggregated to form embryoid bodies to stimulate differentiation and then exposed to BMP2, there is increased expression in SM differentiation as monitored by SM ␣-actin expression (Gossrau et al, 2007).…”
Section: Fgf Wnt and Bmp Signals Can Instruct Pluripotent Cells Towmentioning
confidence: 99%